UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA PADA PENJUMLAHAN DAN PENGURANGAN PECAHAN MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI KELAS V SD 01 KOTA PADANGSIDIMPUAN - Torang Siregar; Suparni; Ahmad Nizar Rangkuti; Lelya Hilda; Sinar Devi Harahap; Hasratuddin (Jurnal Pendekar Nusantara, 2024)
The general aim of implementing the educational unit level curriculum is to make educational units independent and empowered by granting authority to educational institutions and encouraging schools to make participatory decisions in developing the curriculum. Most elementary school teachers often fail to complete the material satisfactorily. After carrying out initial learning at the author's place of teaching at SD Negeri I Padangsidimpuan City class V, they experienced failure in completing with the following results: There were 14 students who got a score of less than 75 or 66.7% with a KKM of 75. Those who got a score of 75 or more there were 7 students or 33.3% with a KKM of 75. In this lesson the researcher carried out activities in accordance with the lesson implementation plan. At first the students looked active and enthusiastic, but when asked to do practice questions they were still confused about how to do it. After researchers analyzed the results of student work (formative tests) in initial learning, it was found that students did not understand the material. Of the 21 students who got a score above the KKM (75), only 7 students or 33.33%. With an average score of 60.0